Gene therapy for nucleus pulposus regeneration by heme oxygenase-1 plasmid DNA carried by mixed polyplex micelles with thermo-responsive heterogeneous coronas. (June 2015) - Feng, Ganjun; Chen, Hongying; Li, Junjie; Huang, Qiang; Gupte, Melanie J.; Liu, Hao; Song, Yueming; Ge, Zhishen
Abstract: Safe and high-efficiency gene therapy for nucleus pulposus (NP) regeneration was urgently desired to treat disc degeneration-associated diseases. In this work, an efficient nonviral cationic block copolymer gene delivery system was used to deliver therapeutic plasmid DNA (pDNA), which was prepared via complexation between the mixed cationic block copolymers, poly(ethylene glycol)- block -poly N -[ N -(2-aminoethyl)-2-aminoehtyl]aspartamide [PEG- b -PAsp(DET)] and poly( N -isopropylacrylamide)- block -PAsp(DET) [PNIPAM- b -PAsp(DET)], and pDNA at 25 °C. The mixed polyplex micelles (MPMs) containing heterogeneous coronas with hydrophobic and hydrophilic microdomains coexisting could be obtained upon heating from 25 to 37 °C, which showed high tolerability against nuclease and strong resistance towards protein adsorption. The gene transfection efficiency of MPMs in NP cells was significantly higher than that of regular polyplex micelles prepared from sole block copolymer of PEG- b -PAsp(DET) (SPMs) in in vitro and in vivo evaluation due to the synergistic effect of improved colloidal stability and low cytotoxicity. High expression of heme oxygenase-1 (HO-1) in NP cells transfected by MPMs loading HO-1 pDNA significantly decreased the expression activity of matrix metalloproteinases 3 (MMP-3) and cyclo-oxygenase-2 (COX-2) induced by interleukin-1β (IL-1β), and simultaneously increased the NP phenotype-associated genes such as aggrecan, type II collagen, and SOX-9. Moreover, the therapeutic effects of MPMs loading pDNA were tested to treat disc degeneration induced by stab injury. The results demonstrated that administration of HO-1 pDNA carried by MPMs in rat tail discs apparently reduced inflammatory responses induced by need stab and increased glycosaminoglycan (GAG) content, finally achieving better therapeutic efficacy as compared with SPMs. Consequently, MPMs loading HO-1 pDNA were demonstrated to be potential as a safe and high-efficiency nonviral gene delivery system for retarding or regenerating the degenerative discs.